Pemanfaatan Teknologi Dalam Pengembangan Ekowisata Di Daerah Pesisir Pantai Lowita Di Desa Wiring Tasi Kecamatan Suppa Kabupaten Pinrang - Nur Syamsu; Ishak Ishak; Eldi Manca; Eva Marin Sambo; Marwah Yusuf; Andi Dahrul; Annas L.Mappiasse (Jurnal Kabar Masyarakat, 2024)
This activity was carried out with the aim of developing knowledge about the use of technology in developing ecotourism in the coastal area of ​​Lowita Beach. This activity was carried out in Wiring Tasi Village, Suppa District, Pinrang Regency on November 4 and 5 2023. This activity was carried out in collaboration with STIEM Bongaya, TJSL, PT PLN (Persero) and the Lowita coastal youth community and was attended by people who live on the Lowita coast. . The method of implementing this activity is packaged in the form of material presentation and discussion as well as practice in the field. Based on the results of the activities that have been described, by using technology such as social media, electronic media and mass media, it is hoped that the promotion of the existence of ecotourism on Lowita Beach will become more widely known by the community, not only locally but also nationally so that it can increase income for the regional government and the community. local from Lowita beach ecotourism management. Apart from that, this activity is expected to provide positive benefits for the community, educate and share knowledge for mutual progress.